PERAN AUDIT INTERNAL DAN KOMITE AUDIT DALAM PENCAPAIAN TUJUAN GOOD CORPORATE GOVERNANCE PADA PT PUPUK SRIWIDJAJA PALEMBANG - Rusmida Hutabarat; Shelly Farida Tobing (Universitas Tridinanti, 2022)
This study aims to determine how the implementation of Good Corporate Governance and how the role of Internal Audit and the Audit Committee in the objectives of Good Corporate Governance at PT. Fertilizer Sriwidjaja Palembang. This research is a comparative research because this study aims to analyze the role of internal audit and the Audit Committee in the objectives of Good Corporate Governance of PT. Fertilizer Sriwidjaja Palembang. The variables and indicators used are internal audit with the main indicators of internal audit implementation (Internal Audit Charter) consisting of the duties and responsibilities of the internal auditor, basic principles of internal audit, internal audit activities, and relations with the audit committee. The audit committee with indicators of the audit committee charter consisting of the duties, responsibilities and authorities of the audit committee, the activities of the audit committee, the relationship between the audit committee and the board of commissioners and the relationship between the audit committee and internal auditors.The data used are primary and secondary data, data collection techniques using interview and documentation techniques. The analytical technique used is qualitative and quantitative analysis methods. The results of the analysis show that the Internal Audit and the role of the Audit Committee related to Good Corporate Governance in general have been carried out well. The Audit Committee and Internal Audit support the objectives of implementing corporate governance, and in accordance with applicable regulations. Keywords: Internal Audit, Audit Committee, Good Corporate Governance